Tricot creates a value network for on-farm testing of crop varieties: Farmers, a crop breeding company, a social enterprise, and a software company reap the benefits of participatory testing - 1000FARMS Platform; Angudubo, Stephen (2025)
This poster highlights how Bayer and One Acre Fund partnered to test maize varieties directly on farmers' fields using the tricot approach, supported by ClimMob, a digital platform developed by MrBot. The collaboration enabled decentralized testing across 120 farmers in Kenya, providing valuable performance insights under real-world conditions. Bayer supplied the seed and funding, One Acre Fund coordinated trial implementation with participating farmers, and MrBot’s ClimMob platform facilitated efficient data collection and analysis. The experience shows how collaborative, farmer-centered approaches can support variety evaluation, strengthen partnerships across the seed system, and generate data that informs breeding and adoption decisions.